Hypoxia Potentiates LPS-Mediated Cytotoxicity of BV2 Microglial Cells In Vitro by Synergistic Effects on Glial Cytokine and Nitric Oxide System - Frey, Daniel; Jung, Susan; Brackmann, Florian; Richter-Kraus, Mandy; Trollmann, Regina (Neuropediatrics, 2015)
Background Microglial activation due to a variety of stimuli induces secretion of neurotoxic substances including inflammatory cytokines and nitric oxide (NO). Clinical studies indicate a cross-link between inflammatory and hypoxia-regulated pathways suggesting that bacterial infections markedly sensitize the immature brain to hypoxic injury.Methods The impact of inflammation and hypoxia on interleukin (IL)-1β, IL-6, tumor necrosis factor α (TNF-α), and NO secretion and microglia-induced cytotoxicity was investigated exposing BV2 cells to lipopolysaccharides (LPS) and hypoxia (1% O2). Cytotoxicity, NO, and cytokine release was quantified by MTS and Griess assays and by enzyme-linked immunosorbent assays, respectively.Results LPS exposure of BV2 cells induced a significant, persistent production of NO, IL-1β, IL-6, and TNF-α. Even after LPS removal, ongoing NO and cytokine secretion was observed. Hypoxia mediated exclusively a significant, short-term IL-1β increase, but enhanced LPS-induced cytokine and NO secretion significantly. In addition, LPS-induced supernatants exhibited a stronger cytotoxic effect in glial and neuronal cells than LPS exposition (p < 0.001). Hypoxia potentiated LPS-induced cytotoxicity.Conclusion Present data prove that LPS-induced soluble factors rather than LPS exposure mediate microglial toxicity under conditions of hypoxia in vitro. Apart from potential protective effects of the hypoxia-inducible transcription factor (HIF)-1α system, activation of proinflammatory pathways may markedly sensitize microglial cells to promote hypoxia-induced injuries of the developing brain.
Keywords: microglia; inflammation; cytokines; hypoxia; HIF-1α; neurotoxicity